Effect of plant growth regulators on flower and bulb production of hippeastrum (Hippeastrum hybridum Hort.) - Jamil, MK; Rahman, M Mizanur; Hossain, M Mofazzal; Hossain, M Tofazzal; Karim, AJM Sirajul (Bangladesh Journal of Agricultural Research, 2016)
The experiment was conducted at the Horticultural research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during October 2008 to July 2009 to investigate the effect of plant growth regulators on flower and bulb production of Hippeastrum. There were ten treatments comprising of three concentrations of three growth regulators viz., IAA (20, 60 and 100 ppm), ethrel (100, 300 and 500 ppm) and GA3 (100, 300 and 500 ppm) along with control (soaked in water). The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Flower and bulb characteristics of Hippeastrum were influenced significantly by different levels of growth regulators. Application of IAA at 60 and 100 ppm and GA3 at 100, 300 or 500 ppm twice as foliar spray at an interval of 30 days promoted the number of bulblets on the treated plants. Ethrel at a concentration of 100 ppm increased the number of flowers per scape (4) and showed earliness in days to flower scape emergence (72.33 days) and first flower open (88.67 days). On the other hand, the biggest size of flower (15.14 cm x 12.44 cm) and flower scape (40.28 cm x 21.95cm) at harvest and the maximum days for flowering (11.50 days) were evident from plants treated with 500 ppm GA3. The highest number of bulblets per plot (40.00), bulbs weight per plot (4056 g) along with bulb yield (40.56 t/ha) were also obtained in GA3 at 500 ppm. Bangladesh J. Agril. Res. 40(4): 591-600, December 2015